Artemis the loyal - Holub, Joan (Holub, Joan. Goddess girls, 2011)
"It's time for the annual Olympic Games, and the four goddessgirls are not happy! It's boys only--and the girls at MOA are not pleased. Led by Artemis, Athena, Persphone and Aphrodite, the ladies of Mount Olympus hatch a plan to get Zeus to open up the games to everyone. Will they succeed--or end up watching from the sidelines again?"--Publisher.